1990
DOI: 10.1099/00221287-136-11-2291
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented antibiotic production by Streptomyces coelicolor A3(2): kinetics and the influence of nutrients

Abstract: ~_ _ _ _ _ _~ _ _ _ _ _ _ _~The production of the pigments actinorhodin and undecylprodigiosin by Stveptomyces coelicolor A3(2) was examined in a chemically defined medium which permits dispersed growth of the organism. The physiological controls on the production of the two pigments were markedly disparate. Actinorhodin production occurred mainly in the stationary phase of batch cultures grown with glucose and sodium nitrate as the principal carbon and nitrogen sources. In the same batch cultures, undecylprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 25 publications
2
59
1
3
Order By: Relevance
“…Effect of nitrogen source on methylenomycin production. Our previous studies on antibiotic production by S. coelicolor A3(2) strain 1147 employed a minimal medium containing an inorganic nitrogen source (12). In none of these experiments was any production of methylenomycin detected, whereas the presence of actinorhodin could be demonstrated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Effect of nitrogen source on methylenomycin production. Our previous studies on antibiotic production by S. coelicolor A3(2) strain 1147 employed a minimal medium containing an inorganic nitrogen source (12). In none of these experiments was any production of methylenomycin detected, whereas the presence of actinorhodin could be demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphate concentration is known to greatly influence antibiotic synthesis in streptomycetes (23,24,29). We had previously found that the production of actinorhodin by S. coelicolor grown on minimal medium containing an inorganic nitrogen source was subject to phosphate regulation (12). Moreover, regulation by phosphate was found to be epistatic to that exerted by the nitrogen source, since it was possible to relieve the ammonium inhibition of the actinorhodin production by lowering the phosphate concentration from 11 to 1 mM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Roles in other ecological interactions should also be considered, e.g. protection against grazers by production of antibiotics, as with Streptomyces (Hobbs et al, 1990), or secretion of siderophores. Siderophores are important in virulence (pathogenicity) expression and development of biofilms by different microbes (Wynn-Williams et al, 2002;Saha et al, 2013).…”
Section: Perception Of Yellow Subaerial Biofilm and Its Potential Rolementioning
confidence: 99%